Increased endothelial activation in recently symptomatic versus asymptomatic carotid artery stenosis and in cerebral microembolic-signal-negative patient subgroups. - O'DONNELL, JAMES; O'NEILL, DESMOND; COUGHLAN, TARA; MCCABE, DOMINICK; DOHERTY, COLIN; HARBISON, JOSEPH; COLGAN, MARY (My University, 2014)
von Willebrand factor propeptide (VWF:Ag II) is potentially a more sensitive marker of acute endothelial activation than von Willebrand factor antigen (VWF:Ag). These biomarkers have not been simultaneously assessed in asymptomatic versus symptomatic carotid stenosis patients. The relationship between endothelial activation and cerebral microembolic signals (MESs) detected on transcranial Doppler ultrasound is unknown.In this multicentre observational analytical study, plasma VWF:Ag and VWF:Ag II levels in patients with ≥50% asymptomatic carotid stenosis were compared with those from patients with ≥50% symptomatic carotid stenosis in the 'early' (≤4 weeks) and 'late' (≥3 months) phases after transient ischaemic attack or ischaemic stroke. Endothelial activation was also longitudinally assessed in symptomatic patients during follow-up. Transcranial Doppler ultrasound monitoring classified patients as MES-positive or MES-negative.Data from 31 asymptomatic patients were compared with those from 46 early symptomatic and 35 late phase symptomatic carotid stenosis patients, 23 of whom had undergone carotid intervention. VWF:Ag II levels were higher in early (12.8 μg/ml; P < 0.001), late (10.6 μg/ml; P = 0.01) and late post-intervention (10.6 μg/ml; P = 0.038) symptomatic patients than asymptomatic patients (8.9 μg/ml). VWF:Ag levels decreased in symptomatic patients followed up from the early to late phase after symptom onset (P = 0.048). Early symptomatic MES-negative patients had higher VWF: Ag II levels (13.3 vs. 9.0 μg/ml; P < 0.001) than asymptomatic MES-negative patients.Endothelial activation is enhanced in symptomatic versus asymptomatic carotid stenosis patients, in early symptomatic versus asymptomatic MES-negative patients, and decreases over time in symptomatic patients. VWF:Ag II levels are a more sensitive marker of endothelial activation than VWF:Ag levels in carotid stenosis. The potential value of endothelial biomarkers and concurrent cerebral MES detection at predicting stroke risk in carotid stenosis warrants further study.
PUBLISHED
Keywords: genes; Ageing; Neuroscience; Age related diseases; Imaging Techniques; Public health